Nepotism in Village Government: A Case Study of the Implementation of Village Government in Serosah, Hulu Kuantan District, Kuantan Singingi Regency, 2015-2021 - Fhisilmi Kaffah; Irda Desbanita; Aini Hafizah (Journal of Public Administration and Government, 2025)
The practice of nepotism characterizes the administration of Desa Serosah in the 2015-2021 period. Nepotism is carried out when there is a recruitment and selection process for a position. Nepotism can be seen from two perspectives, namely from the perspective of the form of the relationship (Kinshipism, Familism, Clanism, Patriotism, Racism, Sexism, Planetism) and from an ethical perspective (Favoritism, Discrimination, Partiality Justice. Merit system). The research method used in this research is qualitative research. The type of research is descriptive qualitative research. The research location is in Serosah Village, Hulu Kuantan District, Kuantan Singingi Regency. The results of the research conducted were that the Serosah Village Head carried out acts of nepotism in the administration of village government. The Serosah Village Head assigns positions to his children, family and relatives and controls the political and economic resources in Serosah Village for personal gain. The Serosah Village Head in the process of recruitment and selection of positions is based on the heredity aspect and is in favor of him.